Human Trafficking : Interdisciplinary Perspectives - Burke, Mary C (Criminology and justice studies series, 2018)
With a range of experts from different disciplines and professions, this text comprehensively explains human trafficking as it exists and is being addressed in the twenty-first century. The first section gives an overview of the issue and contextualizes it within a human rights and historical framework. The second section provides the reader with more detailed, interdisciplinary information about trafficking. The third section, which contains a chapter written by a former FBI agent, focuses on the anti-trafficking movement and addresses international responses to the problem, as well as considerations for working with victims. Human Trafficking closes with a chapter about how trafficking is being addressed and how individuals, larger social groups, and organizations can get involved in putting an end to the crime and to helping survivors. Human Trafficking is essential reading for professionals in law enforcement, human services, and health care, and for concerned citizens interested in human rights and making a difference in their communities. This book is also intended for use in undergraduate and graduate interdisciplinary courses in human trafficking.